INDONESIAN LITERATURE POSITION IN WORLD LITERATURE - Dewi Christa Kobis (STBA LIA - Jakarta, 2019)
This research studies the position of Indonesia literature as a component of literature which can also be categorized as world literature. Due to the fact that Indonesian is sometimes underestimated because its identity as third world nation and this sometimes impacts the way of how foreign researchers value Indonesian’s intellectual products such as Indonesian literature, it is necessary to evaluate Indonesian position in world literature. This research is a qualitative study since it has conducted a library research and it has been completed through document analysis. This study uses Damrosch’s theory of world literature’s characteristics in order to check and to find out whether Indonesian literature can be categorized as world literature or not. Indonesian literary works that have been used as the objects of analysis for this study are Sangkuriang, Mahabharata, and literary works that have been written by Pramoedya Ananta Toer. At the end of this study, it has concluded that Indonesian literature fulfilled the three main characteristics of world literature that have been classified by Damrosch and is able to be categorized as world literature. This clearly demonstrates Indonesian clear position in world literature and also shows that Indonesian literature deserves to be categorized as world literature.